Stiftung Maria und Gerald Fischer-Colbrie - Lentos Kunstmuseum Linz (Linz : Lentos Kunstmuseum Linz, 2003)
Alechinsky, Pierre ; Anzinger, Siegfried ; Arman ; Barek, Bernhard ; Brus, Günter ; Calder, Alexander ; Cibulka, Heinz ; Croissant, Michael ; Export, Valie ; Fleck, Karl Anton ; Frohner, Adolf ; Goeschl, Roland ; Haslecker, Hannes ; Hepworth, Barbara ; Jungwirth, Martha ; Kempinger, Herwig ; Kogelnik, Kiki ; Liberman, Alexander ; Mangold, Robert ; McLean, Bruce ; Moorman, Charlotte ; Mühl, Otto ; Nauman, Bruce ; Nitsch, Hermann ; Oldenburg, Claes ; Paik, Nam June ; Reischenböck, Ernst ; Ringel, Franz ; de Saint Phalle, Niki ; Schmalix, Hubert ; Staudacher, Hans ; Voss, Jan ; Wesselmann, Tom
biog. per kunstenaar
Duits
Exhibition "Stiftung Maria und Gerald Fischer-Colbrie" Lentos Kunstmuseum Linz, 15.10.2003 - 23.11.2003
boek